UN EXTRAÑO EN ESTAS TIERRAS: WALTER BLUMENFELD EN EL PERÚ - León, Ramón (2010)
This paper deals with the presence of Walter Blumenfeld, German Jewish psychologist in the development of psychology in Peru. This scientist, being forced to leave his country because of his Jewish ancestry, should have to adapt himself to unfamiliar surroundings, without knowing the language, and anti-Semitic prejudices abounded and a current psychological effect against experimental psycho logy, he brought to Peru. Already integrated into the peruvian academic environment, published important books on experimental psychology and psychology of learning.